SISTEM AMONG PADA MASA KINI: KAJIAN KONSEP DAN PRAKTIK PENDIDIKAN - Muhammad Nur Wangid (Jurnal Kependidikan, 2009)
The purpose of the study was to show the concept of the among system as a model of education and teaching in documentary sources, and also the realization of the concept in the education and teaching setting. The study involved two designs: one was a study content (documentary) and the other was a qualitative approach. In the first design, the researcher studied written documentary sources of the system among. In the second design, the researcher observed the realization of the system among concepts. The subjects of the study included a member of the Board of Majelis Luhur Taman Siswa, teachers and students of Taman Siswa schools, and also the alumni of Taman Siswa schools. Data were analyzed using qualitative analyses. The results show that the among system of education, the work of Ki Hadjar Dewantara, actually is an educational and teaching system that is complete and comprehensive, and one that can be implemented lifetime. Nevertheless, in the realization on Taman Siswa schools, due to the limitation of facilities, implementation of the among system could not completely.